Beban Kerja dan Efficacy of Prevention terhadap Kepatuhan Perawat Mencuci Tangan dan Memakai APD di Masa Adaptasi Kebiasaan Baru Covid-19 di Puskesmas Binanga Kabupaten Mamuju - supratti supratti; Hasir Hasir; Syafruddin Ali Salaka (Politeknik Kesehatan Kemenkes Mamuju, 2022)
The Covid-19 pandemic has caused changes in all aspects of life, anxiety and panic in society. Transmission of Covid-19 is so fast with varied viral mutations including Alpha (B117), Beta (B1351), Delta (B1617), and the Omicron variant (B11529. Knowledge about covid is growing and various vaccines have been found to break the chain of transmission of Covid-19) 19. Nurses are very at risk of contracting Covid-19 because they provide direct service to patients who show symptoms and those who are asymptomatic, therefore nurses must always obediently wash their hands and wear complete PPE in accordance with standard operating procedures. PPNI states more than 15,000 nurses infected with Covid-19. This study was an observational study using a cross-sectional approach with quantitative analysis. The population of this study used total sampling, namely all 20 nurses at the Binanga Mamuju Health Center. The questionnaire was the instrument used in this study. The analysis was carried out using test Chi-Square Test Yes a significant effect between workload and nurses' adherence to washing hands and using personal protective equipment with a p value of 0.028 Ë‚ 0.05. efficacy of prevention has an effect on nurses' adherence to washing hands and using personal protective equipment with a p value of 0.001 Ë‚ 0.05.